Biomarkers in oncology: overview - Duffy, Joe (Henry Stewart Talks, 2009)
Tumor biomarkers, Role of tumor biomarkers in cancer screening, Aiding cancer diagnosis, Determining prognosis, Therapy prediction, Post-operative surveillance, Monitoring therapy in advanced disease
Reviewed at 2016/01/19